Determining the Compaction Temperature of Warm-Mix Anti-Rutting Asphalt Mixture - Zhaohui Liu; Zebin Liu; You Huang; Yue Cao (Applied Sciences)
In order to study the effect of a warm-mix agent on the compaction characteristics of an anti-rutting asphalt mixture, this study compared the compaction temperature of an anti-rutting asphalt mixture with different warm-mix-agent contents from two aspects: asphalt viscosity and asphalt mixture voids. Based on the rheological properties of asphalt, the optimal content of the anti-rutting agent was first determined as 6% by the weight of asphalt. Four warm-mix-agent contents of 0% (control group), 1%, 2%, and 3% were designed. The viscosity–temperature curve of the warm-mix anti-rutting modified asphalt was obtained by the Brookfield viscosity tests. After that, AC-20 standard Marshall specimens were prepared to conduct a series of consecutive temperature compaction tests. The voids were calculated based on the bulk density of the specimen measured by the saturated surface-dry method. Industrial Computerized Tomography (CT) was employed to further quantify the internal voids. Two voids–compaction temperature curves were constructed based on the saturated surface-dry and CT results, respectively. The comparative results show that significant differences exist between the compaction temperatures obtained from the three curves. The viscosity–temperature curve shows that when the warm-mix agent is increased from 0% to 3%, the compaction temperature only declines about 7.9%. However, the voids–compaction temperature curves from saturated surface-dry and CT, respectively, indicate a temperature decrease of 22.7% and 19.2%. This is because a warm-mix agent will interact with asphalt, resulting in a decrease in asphalt intermolecular adsorption, whereas an anti-rutting agent mixed with asphalt will increase the degree of cross-linking and aggregation between asphalt molecules. Both additions have a certain impact on the viscosity of the asphalt binder; thus the traditional method of using the asphalt viscosity–temperature curve to determine the compaction temperature of warm-mix anti-rutting asphalt mixture has become ineffective. It is suggested to use the equal voids method to determine the compaction temperature of warm-mix anti-rutting asphalt mixtures.